Analysis Of Monetary Policy Transmission Through Asset Price And Inflation Expectation Channels In Indonesia - Rifqa Pratiwi Balqish, Ahmad Albar Tanjung, Irsad Lubis (International Journal of Management, Innovation, and Education, 2022)
The Objectives of this research are (1) to find out the effectiveness of the mechanism of monetary policy transmission by reviewing some required to achieve the final goal namely inflation by using the asset price and inflation expectations. (2) to find out determine which is more effective in realizing the final inflation target. This research uses regression models of Structural Vector Autoregression (SVAR) to estimate the effects of the mechanism of monetary policy transmission on inflation through the asset prices channel and the inflation expectation channel and also review some required to achieve the final goal namely inflation. The data used in this research are time series quarterly from 2010 to 2021. The secondary data used is sourced from the annual report officially published on the website of Bank Indonesia, the Statistics Center Agency, and the Ministry of Investment/BKPM. The variables used to estimate the mechanism of monetary policy transmission through the asset price channel are the BI rate, interest rates of the money market among banks, composite stock price index, real investment, output gap, and inflation. The variables used to estimate the mechanism of monetary policy transmission through the inflation expectation channel are the BI rate, inflation expectations, output gap, and inflation. The results demonstrate the effectiveness of the mechanism of monetary policy transmission through the asset prices channel to achieve the final target on inflation each of which requires 6 (six) quarters. Meanwhile, the effectiveness of the mechanism of monetary policy transmission through the inflation expectations channel to achieve the final target on inflation each of which requires 4 (four) quarters. The results also show that the inflation expectation channel is more effective than the asset price channel in realizing the final inflation target.